Assistance, Simple Financial Bookkeeping, for Culinary MSMEs, in front of TMPN Kalibata in Duren Tiga Village, Pancoran South Jakarta - Wastam Wahyu Hidayat; Widi Winarso; Rachmat Pramukty (Jurnal Pengabdian Masyarakat Formosa, 2023)
This community service activity aims to assist to provide understanding, especially related to simple financial accounting matters to improve Culinary MSME businesses. Culinary MSME actors generally only keep simple records in the form of income and expenses, but many things are overlooked in recording so that they appear to generate large profits but many expenses are not recorded properly. As a result, the records carried out do not reflect the actual financial condition of the business. Community Service activities carried out are (a) Education on the importance of good financial bookkeeping, and (b) Training on making simple MSME financial bookkeeping.